The Moderating Role of Agricultural Product Categories in the Relationship Between Digital Marketing Competencies and Marketing Performance - Nofal Supriaddin; Astil Harli Roslan; La Ode Hamida (Journal of Global Innovations in Agricultural Sciences)
Digital transformation has become a critical driver of competitiveness in various industries including agriculture. With challenges such as limited market access and low competitiveness of agricultural products, digital marketing competencies have emerged as essential for improving business performance. This study examines the impact of Digital Marketing Competencies on Marketing Performance and Continuance Intention. It focuses on the mediating role of Marketing Performance and the moderating influence of Agricultural Product Categories. This study involved 279 Micro, Small, and Medium Enterprises (MSMEs) spread across six provinces on the island of Sulawesi: Central Sulawesi, South Sulawesi, Southeast Sulawesi, North Sulawesi, Gorontalo, and West Sulawesi. Data was collected through online questionnaires distributed via e-commerce platforms and analyzed using Jamovi software. The study explored direct, mediated, and moderated relationships across three agricultural product categories, Fresh, Processed, and Support Products. Additional analysis using One-Way ANOVA was carried out to evaluate differences in moderating effects based on product categories. The findings reveal that Digital Marketing Competencies positively influence both Marketing Performance and Continuance Intention. This relationship is strengthened through the mediating role of Marketing Performance, demonstrating its importance in translating digital marketing efforts into sustainable outcomes. Agricultural Product Categories were found to moderate the effectiveness of digital marketing, with Support Products such as fertilizers and farming tools showing the highest marketing performance. This reflects their strong market appeal compared to Fresh Products, which face greater challenges, and Processed Products, which have fallen with no significant differences compared to the other categories. These results highlight the importance of tailoring digital marketing strategies to specific product types. To remain competitive, agricultural business operators need to adopt innovative marketing approaches, particularly for Fresh and Processed Products, while leveraging the inherent strengths of Support Products. By optimizing digital marketing competencies, businesses can achieve improved performance and sustainable growth in the agricultural sector. Keywords: Agriculture entrepreneurs, digital transformation, e-commerce platform, marketing competitiveness, digital marketing, continuance intention .